Implementation of an Expanded Promotion Mix in Increasing New Student Acceptance of SMK Wira Harapan, Badung, Bali - Maryanthi, Ni Kadek; Junaedi, I Wayan Ruspendi; Utama, I Gusti Bagus Rai; Santoso, R Tri Priyono Budi (Eastasouth Institute, 2024)
The objective of this study is to ascertain the impact of Digital Marketing, Word of Mouth Communication, and door-to-door advertising on the decision-making process of students while selecting Wira Harapan Badung Bali Vocational School. The research design used is quantitative causality. The sample that will be used in this research is 143.7 or 150 respondents. Data analysis in this study used multiple linear regression. The research findings indicate that internet marketing, word of mouth, and door-to-door advertising have a substantial and favorable impact on students' decision-making process on their choosing. Digital marketing, WOM and door to door promotions simultaneously influence voting decisions. It is recommended to pay attention to the content shared in digital marketing, increase WOM by interacting more with consumers and consider door to door promotions which can increase the decision to choose Wira Harapan Vocational School.